تقنين اختبار المناولة القريبة بباطن القدم على المربعات المتداخلة المقرونة ببعض مظاهر الانتباه للاعبي كرة القدم الصالات - الجنابي, عبدالمنعم أحمد جاسم; النعيمي, محمد خليل ابراهيم (Sulaimani Journal for Humanities, 2018)
The search problem has been identified in: The lack of proficiency tests for the nearby passing skill of footbones for club futsal players depends primarily on the nature of their application to certain aspects of attention (attention span, attention distribution and attention shift) that can be relied upon to evaluate these aspects. The study aimed at: -Standardization of the whip passing test from the head level, which depends on the performance of some aspects of attention to overlapping circles designed for handball players on the futsal players lounges. -Setting tables and standard levels to test the nearby passing of the footbone of the intervening square boxes on the futsal players lounges. The researchers used the descriptive method in the survey method. The research community has determined the players of Iraq for the excellent grade of football for the club which is (324) players representing (22) clubs and the sample was chosen by the deliberate way and the sample (204) players representing (14) clubs, The sample consisted of (11) players and (sample of scientific bases) reached (30) players while (sample of rationing) (163) players represented %79.901of sample Total Research. Data collection methods- : The researchers used the questionnaire and tests as well as the sample. The researchers used the following statistical methods (percentage, arithmetic mean, standard deviation, covariance, ka2 test, torsion coefficient, simple correlation coefficient (Pearson) and standard (6-δ ). The researchers reached the following conclusions: 1- Arrhythmia: The near-foot-passing test of the footbone has been reached on the overlapping circles with some attention (volume, distribution, divert attention) assigned to the football players lounges. 2- Standards and standards for standardized testing have been established.